PENERAPAN MODEL PEMBELAJARAN COURSE REVIEW HORAY UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI SISTEM KLASIFIKASI MAKHLUK HIDUP PADA KELAS X SMA NEGERI 14 AMBON - Christin Tulaseket; F Leiwakabessy; Dominggus Rumahlatu (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: This study aims to determine the effect of the application of the learning model of the horay course review to improve student learning outcomes of teaching material on the classification system of living things in class X of SMA Negeri 14 Ambon. Method: Samples from this study were students of class X1 with 23 students. This type of research is descriptive research to see student learning outcomes which consists of 3 factors, namely physical, cognitive and psychomotor. The instruments used in this study were test instruments in the form of initial tests and final tests. Results: The results of this study show that there is a significant effect by using the learning review horay learning model on improving student learning outcomes during the implementation of the learning model of the course review horay. Conclusion: Based on the results of the study it can be concluded that the use of the Course Review Horay learning model can improve the learning outcomes of class X1 students at SMA Negeri 14 Ambon. This can be seen from the results of the final test which is very satisfying from the results of the initial test. Presentation of student grades during the initial test is 13% and the final test score reaches 100%.